Admission Lipid Profile and Discharge Outcome in Ischemic and Hemorrhagic Stroke (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2023)
Background: Changes in the lipid profile have been suggested as a risk factor for developing ischemic stroke. Their role in hemorrhagic stroke is not clear. The study aimed to evaluate the lipid profile levels and discharge outcomes of patients who were admitted to a tertiary hospital in Bangladesh and also to determine the difference in the lipid profile of patients with ischemic and hemorrhagic stroke.Materials and methods: This retrospective analytical study included 65 hospitalized stroke patients from the Neurology Unit of Chittagong Medical College Hospital. Data regarding age, sex, risk factors of stroke, lipid profile [Total Cholesterol (TC) Triglyceride (TG) Low-Density Lipoprotein cholesterol (LDL-C), and High-Density Lipoprotein Cholesterol (HDL-C)] levels, and discharged outcomes [Favourablemodified Rankin Scale (mRS)score £2 and unfavourable-mRS >2] were extracted from the register and compared between ischemic and hemorrhagic stroke patients.Results: Out of 65 patients, 55 (84.6%) had ischemic and 10 (15.4%) had hemorrhagic stroke. Hypertension (67.7%), smoking (50%), diabetes (40%), and family history of stroke (38.5%) were common risk factors. The most common lipid abnormality was high LDL-C (86.2%), followed by low HDL-C (63.1%), high TG (47.7%), and high TC (35.4%). There was no difference in the lipid profile ofischemic and hemorrhagic stroke patients. Forty-seven (72.3%) patients were in poor functional status during discharge and discharged outcome was not associated with admission lipid profile. Compared to patients with unfavorable outcomes, patients with favorable outcomes at discharge were significantly younger, had shorter durations of hospitalization, had lower mRS scores at admission.Conclusion: Dyslipidemia in the form of high LDL-C and low HDL-C were common in stroke patients be it infarct or hemorrhage. There was no difference in the lipid profile of the two categories of stroke.Chatt Maa Shi Hosp Med Coll J; Vol.22 (1); January 2023; Page 23-27